Le postillon de Lonjumeau Opéra-comique in three actes (1836) - Adam, Adolphe 1803-1856 (Naxos Rights (Europe) Ltd., 2020)
Adolphe Adam's Le Postillon de Lonjumeau was a great success at its premiere in 1836, and, along with the ballet Giselle, has remained one of the composer's most popular works. Following the great French tradition, this opéra-comique has it all: 18th century Rococo Parisian glamour and a perilous love story involving the dashing and flirtatious Chapelou and his opposite, the powerful and clever Madeleine
Filmed on 5 an 7 april 2019 at the Opéra Comique, Paris, France
A production by the Opéra Comique in co-production with Opéra de Rouen Normandie with the support of Mister G.F.
Bildformat: 16:9
Keywords: Operas; Film; Blu-Ray-Disc